In vitro evaluation of some pyrethroid acaricides against Amblyomma cajennense (Fabricius, 1787). - Bittencourt, Vânia Rita Elias P.; Massard, Carlos Luiz; Grisi, Laerte (Pesquisa Agropecuaria Brasileira, 2014)
The synthetic pyrethroids alphamethrin, deltamethrin, flumethrin and fenvalerate were evaluated in vitro against the horse tick Amblyomma cajennense. The methodology used included the immersion of different stages of the tick (nonengorged and engorged larvae, nonengorged and engorged nymphs, nonengorged and engorged adults) in different concentration of the pyrethroids. Regression analyses and determination of inibition concentration (Cl) 50 and 90 were performed. Nonengorged stages were more susceptible than the respective engorged stages. Amblyomma cajennensewas found to be less susceptible to the pyrethroids than the cattle tick Boophilus microplus, in vitro.